Cryopreservation of single-sperm: where are we today? - Shasha Liu; Fuping Li (BMC, 2020)
Abstract Background Patients with severe oligospermia and nonobstructive azoospermia have very limited numbers of viable sperm in their epididymal and testicular samples. Thus, cryopreservation of their sperm is performed to avoid repeated sperm retrievals and to preserve their sperm from any side effects of any treatment regimens. Main body The development of intracytoplasmic sperm injection technology has extended the therapeutic capacity of assisted reproductive technology for men with azoospermia via the surgical or percutaneous isolation of sperm from the testis/epididymis. The conventional cryopreservation techniques are inadequate for preserving individually selected sperm. The technique for freezing single sperm was first developed in 1997 and has been explored from the perspective of frozen carriers, freezing programs, and cryoprotectant formulations. Among these methods, advances in frozen carriers have directly improved single-sperm freezing technology. In this review, we evaluate the different technologies for the cryopreservation of single sperm by discussing the advantages and disadvantages of different freezing methods, their clinical applications, and the outcomes for a range of frozen carriers. Conclusion Our review article describes the latest and current technologies implemented for the cryopreservation of single sperm that could potentially benefit patients with severe oligospermia and who rarely have any sperm in their ejaculate. This review provides a platform to understand the process and pitfalls of single-sperm cryopreservation to ensure further improvements in the cryopreservation technology in future studies.